Danlu tongdu tablets: Preclinical safety evaluation and mechanism of hepatotoxicity - Zhang, Haijing; Yang, Yifei; Guo, Feifei; He, Rong; Gao, Shuangrong; Cao, Chunyu; Zhao, Chunhui; Xia, Bing; Xu, Qihua; Gong, Ping; Wang, Lifang; Su, Ping; et al. (Frontiers in Pharmacology, 2022)
Danlu tongdu tablets (DLTD) is a listed Chinese patent medicine collected in the Pharmacopoeia of the People’s Republic of China (version 2020). This prescription has been applied in clinics in China for lumbar spinal stenosis and lumbosacral disc herniations. The wide application of Danlu tongdu in therapy has raised some clinical adverse reactions, such as significant elevation of alanine transaminase (ALT) and aspartate transaminase (AST) in individual patients after use. The present study aimed to investigate the safety of Danlu tongdu and analyze its adverse effects on the liver. The maximum feasible dose (MFD) was used to carry out the acute toxicity tests. Mortality, adverse effects, body weight and food consumption were recorded for up to 14 days post treatment. In the 6-month chronic toxicity test, sprague-dawley rats were randomly divided into four groups according body weight, the experimental groups were administrated to rats at the concentrations of 1.67, 3.34 and 6.67 g/kg/day, whereas the control group was received the ultrapure water (vehicle) only, 10 ml/kg, once a day. The animal’s body weight, food consumption was monitored weekly. In addition, their hematological and biochemical parameters, body and organ weights and histopathology, were all measured at specific observation time points. Additionally, we further explored the adverse effects mechanism of Danlu tongdu on the liver through transcriptome analysis. No deaths or substance-relative toxicity were observed in the acute toxicity study or the 6-month chronic toxicity study with doses of 1.67 g/kg and 3.34 g/kg, respectively. We found that mild hypertrophy and hyperplasia of hepatic interlobular bile ducts were detected in some rats with doses of 6.67 g/kg after repeated oral administration of Danlu tongdu for 13 and 26 weeks, but the above changes in liver were reversible. The results of transcriptome sequencing showed that Danlu tongdu had a significant effect on cytochrome P450 enzymes in rat liver, especially cytochrome P450 1 (CYP1) subtype. Therefore, the toxic target organ of Danlu tongdu is the liver and the mechanism of mild liver injury is closely related to the up-regulation of cytochrome P450 1A1 (CYP1A1) and cytochrome P450 1A2 (CYP1A2) expression.